DIGITAL OSCILLATOR CIRCUIT WITH AN EXTENDED REPETITION PERIOD OF A PSEUDO-RANDOM PULSE SEQUENCE - Zaurbek, А.; Dzhuruntaev, Д.З. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
In this paper, we consider the issue of upgrading the circuit of a digital generator of a pseudo-random pulse sequence, which can be used to create cryptographic encryption algorithms. The need to modernize the digital generator circuit is associated with an increase in the number of pseudorandom pulse train sequences generated at its output and with pseudorandom intervals between them. To achieve this, a small number of additional elements are included in the circuit of a digital pseudorandom sequence of pulses based on a five-digit shift register with linear feedback. Based on the modernized circuit of a digital generator of a pseudorandom sequence of pulses and an active secondorder Slenlen-Key RC low-pass filter, a digital acoustic noise generator is constructed, which, unlike the prototype, has a truly random output signal over a period of ~ 4 * (2N - 1), subject to circuit simplicity.